PERI-IMPLANTITIS- TIPS IN SURGICAL APPROACH - Stojcevska, Daniela Cvetanovska; Veleska Stevkovska, Daniela; Aleksandrovska, Ana; Evrosimovska, Biljana; Micevski, Bobi; Trajkovski, Branko (Journal of Morphological Sciences, 2022)
Bacterial colonization of the peri-implant sulcus, development of inflammation of the soft peri-implant tissues, followed by progressive loss of the peri-implant bone results in  periimplantits development and subsequent implant failure. The aim of this case study is to prove that successful treatment of peri-implantitis integrates conservative and surgical approach with the accent on decontamination of the implant surface, complete elimination of microorganisms and their toxins, stabilization of progressive bone loss and regeneration of bone tissue.  Case report :  In this paper initial and surgical treatment of a periimplant case of 43 years old, non-smoker, in good general health is described. A nonsurgical periodontal supportive therapy was firstly conducted to reduce the inflammation, followed by the surgical treatment of the defect. After mechanical and chemical decontamination with chlorhexidine 0.2%, a regenerative approach consisting in the application of bovine bone mineral (Cerabone) and a CTG membrane  was performed. An antibiotic therapy was associated with the treatment according to molecular analysis findings for periodonthopatogenic bacteria. The decision for following the newest up-dates of the surgical protocols for periimplantitis results in predictable clinical improvement in the cases with periimplantitis.    Keywords:   periimplantits, GBR, CTG.